Spatial–temporal analysis of patient complaints in Shanghai from 2015 to 2022 - Gan Wang; Chaowei Wu; Ye Yao; Tiantian Zhang (BMC Health Services Research)
Abstract Objective Patient complaints are crucial for improving the service quality of hospitals and healthcare professionals as well as enhancing patient satisfaction. The 12320 and 12345 hotlines in Shanghai are key platforms for receiving public health complaints. Understanding the temporal and spatial changes in the growth rate of patient complaints in Shanghai is essential for resource allocation and service quality improvement. Methods This retrospective study investigated the spatial distribution characteristics of the growth rate of patient complaints in Shanghai’s sub-districts from 2015 to 2022, involving a total of 326,147 patient complaint cases. We used ArcGIS 10.2 to analyze the annual trends in complaint volume, perform spatial autocorrelation analysis, hot-spot analysis (Getis-Ord Gi*), and content analysis based on the Healthcare Complaint Analysis Tool (HCTA). Results The volume of patient complaints showed a continuous upward trend from 2015 to 2022. The Moran’s Index for the two periods of 2015–2019 and 2015–2022 was 0.020 (P = 0.036) and 0.045 (P = 0.001), respectively. Patient complaints exhibited strong spatial clustering effects in certain street areas, particularly in the western suburbs, where the growth rate of complaints was more severe than in central urban areas. The top three types of complaints in focus areas in 2022 were environment, safety, and institutional processes, accounting for 45.93%, 13.73%, and 18.24%, respectively. Hotspot areas were concentrated in the western and southwestern parts of Shanghai, with the main complaint stages occurring during admission, examination and diagnosis, and surgery and procedures. Conclusion This study explored the methodological approach to studying the temporal and spatial distribution of patient complaints. Shanghai should focus on healthcare complaints from the western and southwestern suburbs. Future resource allocation and service quality improvement should target these high-complaint regions and frequently complained issues to enhance patient satisfaction and overall healthcare quality.